Universities Management in Nigeria: Problems, Prospects and Solutions - Ajayi R. A; Ogunode N. J. (International Journal on Integrated Education, 2022)
Nigerian higher education is the largest in Africa. The Nigerian higher education include Universities and Inter-University Centres such as the Nigeria French Language Village, Nigeria Arabic Language Village, National Institute of Nigerian Languages, institutions such as Innovation Enterprise Institutions (IEIs), and Colleges of Education, Monotechnics, Polytechnics, and other specialized institutions such as Colleges of Agriculture, Schools of Health and Technology and the National Teachers' Institutes (NTI). The public universities in Nigeria are not performing well. The management of public universities is plagued with many problems. This paper examined the various problems hindering the effective management of public universities. Secondary data and primary data were employed in the paper. The paper identified inadequate funding, inadequate academic staff, inadequate facilities, insecurity, strike actions, brain-drain and corruption as challenges hindering management of public universities in Nigeria. Based on these problems, it was recommended that the government should increase the funding of public universities.